2020
DOI: 10.1007/s00428-020-02833-5
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of tissue TLR2 and TLR4 in colorectal cancer

Abstract: Colorectal cancer (CRC), the second most common cancer globally, resulted in 881,000 deaths in 2018. Toll-like receptors (TLRs) are crucial to detecting pathogen invasion and inducing the host’s immune response. This study aimed to explore the prognostic value of TLR2 and TLR4 tumor expressions in colorectal cancer patients. We studied the immunohistochemical expressions of TLR2 and TLR4 using tissue microarray specimens from 825 patients undergoing surgery in the Department of Surgery, Helsinki University Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
2
17
1
Order By: Relevance
“…Very few studies exist describing the role of TLRs in CRC. We previously demonstrated that patients with lymph node-positive disease with a strong tissue expression of TLR2 exhibited a better DSS [11]. The current study supports this finding, since CRC cases with a high TLR2 expression exhibited a better prognosis across the entire cohort.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Very few studies exist describing the role of TLRs in CRC. We previously demonstrated that patients with lymph node-positive disease with a strong tissue expression of TLR2 exhibited a better DSS [11]. The current study supports this finding, since CRC cases with a high TLR2 expression exhibited a better prognosis across the entire cohort.…”
Section: Discussionsupporting
confidence: 88%
“…TLRs have not been extensively investigated in CRC, with TLR4 representing the most studied TLR in CRC. In a previous study, we revealed that Dukes B patients with strong TLR4 tissue immunoexpression exhibited a worse prognosis, while a strong TLR2 tissue immunoexpression was associated with a favorable prognosis in Dukes C patients [11]. In another study, we demonstrated that a strong TLR5 tissue expression represents an independent positive prognostic factor among CRC patients [12].…”
Section: Introductionmentioning
confidence: 97%
“…patients was associated with a worse disease (48). Another study showed that stimulation of TLR2 promotes TLR2 positive squamous carcinoma cell growth (49).…”
Section: Oncogenic Nature Of Grp94 Clientsmentioning
confidence: 98%
“…In CRC patients, TLRs have not been widely investigated. In our previous study, Dukes B CRC patients with a strong TLR4 tissue expression exhibited a worse prognosis, while Dukes C CRC patients with a strong TLR2 expression experienced a better prognosis [14].…”
Section: Introductionmentioning
confidence: 83%